Systems, Software and Services Process Improvement 19th European Conference, EuroSPI 2012, Vienna, Austria, June 25-27, 2012. Proceedings - Winkler, Dietmar; O$1 (BConnor, Rory V.s; Messnarz, Richard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume constitutes the refereed proceedings of the 19th EuroSPI conference, held in Vienna, Austria, in June 2012. The 29 revised papers presented in this volume were carefully reviewed and selected. They are organized in topical sections on SPI and business factors; SPI lifecycle and models; SPI assessment and quality; SPI processes and standards; SPI in SMEs; SPI and implementation; creating environments supporting innovation and improvement; standards and experiences with the implementation of functional safety; business process management; SPI in SMEs - a project management perspective.
Keywords: Computer science; Software engineering; Information systems; Information Systems; Computer Science; Software Engineering; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Software Engineering/Programming and Operating Systems